Advancing stone treatment: the transformative impact of flexible navigable suction ureteral access sheath (fans) for inferior calyx calculi (<2 cm) - Xu, Xiang yun; Tu, Hong jian; Luo, Qing hua; Wei, Wen; Cheng, Fan qi; Cao, Lei hua (Frontiers in Urology, 2026)
ObjectiveThis study aimed to assess the efficacy, safety, and stone-free rates (SFR) of the application of a flexible navigable suction ureteral access sheath (FANS) in patients undergoing retrograde intrarenal surgery (RIRS) for inferior calyx calculi (<2 cm).MethodsA retrospective analysis of the clinical data of 111 patients who underwent treatment for inferior calyx calculi at Nanchang People’s Hospital between January 2023 and October 2024 was performed. Patients undergoing RIRS with laser lithotripsy were evenly distributed into two groups: FANS with continuous flow lithotripsy in ureterorenolithotripsy procedures (F-Group), a conventional sheath in ureterorenolithotripsy procedures (C-Group).ResultsA significantly greater stone clearance rate (96.23% vs. 81.03%, p=0.017) and shorter operative time (37.81 ± 6.07 min vs. 46.59 ± 6.36 min, p<0.001) were observed with the F-Group. Basic attributes, including demographics of patients and stone properties, the infundibulo-pelvic angle (IPA), length of hospital stay, and complications, were compared between the groups and found to be approximately the same.ConclusionsFANS significantly improves SFR without increasing postoperative complications or negatively affecting recovery, offering a promising alternative to conventional sheaths in ureterorenolithotripsy procedures for inferior calyx calculi. FANS improves kidney stone surgery outcomes, is feasible and safe for inferior calyx calculi (<2 cm).